Fel d1 Blocking Antibodies: A Novel Method to Reduce IgE-Mediated Allergy to Cats - Ebenezer Satyaraj; Peichuan Sun; Scott Sherrill (Journal of Immunology Research)
Fel d1 is an important allergen produced by cats that causes IgE reactions in up to 95% of cat-allergic adults. Immunotherapy to reduce human allergy to cats has demonstrated that people have the capacity to produce allergen-specific neutralizing antibodies that block IgE-mediated allergic responses. We wished to determine if “blocking” antibodies could be used to reduce the IgE binding ability of cat allergens prior to their exposure to humans. Here, we describe the characterization of Fel d1-specific antibodies. We demonstrated the efficacy of a rabbit polyclonal and an allergen-specific chicken IgY to bind to Fel d1 in cat saliva and block Fel d1-IgE binding and IgE-mediated basophil degranulation. Fel d1 blocking antibodies offer a new and exciting approach to the neutralization of cat allergens.